Kinetics of hydrocortisone sodium phosphate penetration into the human aqueous humor after topical application. Issue 12 (26th October 2021) - Cagini, Carlo; Muzi, Alessio; Castellucci, Greta; Ragna, Giulia; Lupidi, Marco; Alabed, Husam B. R.; Pellegrino, Roberto Maria
Abstract: Aim of the study: Hydrocortisone is a soft steroid with low anti‐inflammatory properties and a short duration of action, used to manage several ocular conditions. The clinical benefits and side effects associated with hydrocortisone are well documented, but its basic pharmacokinetic in the eye is yet to be fully elucidated. The purpose of this study is to investigate the anterior chamber penetration capabilities of hydrocortisone when used in different concentrations as eye drops treatment. Materials and Methods: This is a double‐blind, single‐centre, randomised clinical trial performed at the Department of Medicine and Surgery of the University of Perugia (Italy) on consecutive patients who undergone phacoemulsification with intraocular lens implantation. Patients were randomly assigned on the morning of surgery to receive a single instillation of 0.33% (group A) or 0.001% (group B) hydrocortisone sodium phosphate solution. Group of patients C did not receive any treatment and was used to measure the hydrocortisone endogenous levels. Before surgery, one aliquot of aqueous humor for each patient was aspirated. The time of collection for each sample was recorded. Hydrocortisone concentrations were then stratified into six interval classes of 30 minutes each. Results: The mean concentration of hydrocortisone was significantly higher in group A (25.2 ± 12.4 ng/mL) compared with group B (7.11 ± 1.51 ng/mL) and compared with the mean hydrocortisone endogenous levels (3.92 ± 1.18 ng/mL) ( P < .0001). No statistically significant differences of hydrocortisone mean concentrations between group B and the mean endogenous levels were found. Conclusions: Considering the frequent need for prolonged topical steroid therapies and the possible consequent undesirable side effects, ophthalmologists should consider the lowest clinically effective dose of hydrocortisone useful to obtain the desired therapeutic effect and in an adequate time, to minimise the amount of steroids into the anterior chamber and to avoid side effects like intra‐ocular pressure increase or cataract development.